The Influence of a Peer Support Camp on Mitigating Emotional Distress in Siblings of Children With Cancer. (March 2022) - Gregory, Donna; Van Puymbroeck, Marieke; Crowe, Brandi; Garst, Barry; Amylon, Michael
Background: Siblings of children with cancer often experience anxiety and posttraumatic stress symptoms (PTSS), which negatively impact their self-esteem due to emotionally upsetting circumstances. The purpose of this longitudinal quantitative study was to investigate changes in anxiety, PTSS, and self-esteem of youth who participated in a peer support camp for siblings of children with cancer.Methods: A longitudinal study examined changes over time. Data were collected from 32 sibling surveys pre-, post-, and three months after camp. Siblings completed assessments to measure anxiety, PTSS, and self-esteem. A repeated measures ANOVA or Friedman Test was conducted to identify changes across the three data points for each outcome measured. Post hoc comparisons using paired sample t-tests or Wilcoxon Signed-Rank tests were conducted.Results: Significant improvements in anxiety; T1 and T2 ( p < .000); T1 and T3 ( p < .000). Significant decrease in PTSS; T1 and T2 ( p = . 001); T1 and T3 ( p = .011). Significant improvement in self-esteem scores for older participants (ages 10–16); T1 and T2 ( p < .000). Significant improvement in self-esteem for younger participants (ages 7–9); T1 and T3 ( p = .005).Discussion: The data generated in this study expand knowledge about the influence of peer support camps on reducing the emotional distress of siblings of children with cancer. The findings warrant further research on the long-term impact of such camps, the value of repeated participation, differences between bereaved and nonbereaved siblings, the phase of the cancer experience, and elements of the camp that have the most impact.